Aids according to the view of the de af young adult people - Bento, Isabel C.B.; Bueno, Sonia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: this paper divulges a study about AIDS, realized with deaf youngful adults, from a schollroom for young and adults, at nocturnal, froma interior town of Brazil (São Paulo State). Objective: the aim consisted in to observe the deaf’s comprehesion about AIDS, to offer educative actions with them, and to eliminate their doubts and inquietudes. Methodos: the data acquisition consisted in the accomplishment of personal and col-lective interviews, by means of Brazilian Language of Signals (In portuguese, LIBRAS: Língua Brasileira de Sinais). There was the attendance of a LIBRAS instructor. The interviews were recorded at video and, afterwards, they were transcribed. At this process, there was the need of applicationof a person communicating observation, in order to unveil better their scholar life. There was the realization of collective actions too. The data wereregisted in the research daybook. Therewith, it was possible to analyse the data in a qualitative manner, through thematic analysis; as according to aMinayo’s writing. In this research, there was the utilisation of the search-action system (In portuguese: pesquisa-ação) by Paulo Freire, an importantbrazilian educator. Results: nine individuals were listened: six male deaf vollunteer and three famale ones, among 18-25 years old, and all follow acourse at secondary scholl (brazilian scholar third level). Seven are single and the others two compose a concubined couple. They are manual labourers or actuate in subaltern jobs, some of them have no employment; others are pensioner. Everybody are Roman Catholic. They frequent a associa-tion for deaves during one and three years, since its foundation. The researcher noticed the deaf presents hardness to comprehend the proper mannerto struggle against the knowledges. This evidence claims some methods which adjust the data to comprehension. They entail AIDS to promiscuousness, drugs, death, proximity with blood and something to be avoided; they know the needs to avoid the illness, but they have no suitable information about the infection manners. Another search important datum: the deaves understand which AIDS is a visible thing, for instance: the emaciation.Conclusion: the scholar delay, whereas their age group, means very difficulty to follow the course. The cause consists in the following olden conception of brazilian scholls: the insertion of the pupil at the society depends on the oral language necessarily, in detriment of knowledges. Although the difficulties, the deaves obtain data about AIDS reasonably. Nevertheless, the researcher believes there is the needs the accomplishment of an adapta-tion course for deaves, that is, a kind of the levelling, in order to objectify at least decision-making about prevention of AIDS. There is the needs thelevelling contents are adjusted for deaves, because they have no cognitional shortage due to deafness. It is important the language is ministered con-veniently: it is necessary to improve the informations and to take advantage of optimization of others feelings which deaves have: sight and tactilesense. The practice unveils some results very promising, when improved visual exercises were utilized properly. They are activity which enable thedeaves to become multiplying agents by means of the informations which they received. Education and Health Professionals need to worry about peculiarities of the deaf language; in this manner, the deaf culture need to be respected in its singularities. The unique difference between deaves andanother people consists in non-use of hearing. Obviously, therefore the deaves are not less important than somebody else; they are only different. Dueto this dissimilarity, they need to be respected and attended, because they are able citizens and have the same rights, at a just and equalitarian society.